Danielson teaching framework as game changer for teaching fiqh muamalat: a way forward - Abdullah, Mohammad Ridhuan; Ahmad Zabidi, Radin Seri Nabahah (University of Lampung, Indonesia, 2023)
Danielson Teaching Framework (DTF) is a proven effective framework to measure learning and teaching efficiency that has been used extensively in North America. However, it was found that DTF was never tested in teaching and learning Islamic Education. On the other hand, there is a lack of research in terms of an effective teaching approach to encapsulate the Fiqh Muamalat knowledge although it is important in the Islamic education and Islamic banking sectors. This study tested DTF and its dimensions to Fiqh Muamalat ‘s teaching at various higher education institutions in Kelantan, Malaysia. The study was also concerned how the DTF elements could improve students' learning. This study explored 4 dimensions of DTF which are planning and preparation, classroom environment, instruction and professional responsibilities. 313 participants were tested through a questionnaire developed based on DTF and were analyzed using descriptive analysis. The results suggested and implicated that DTF is a good teaching evaluation framework to see teachers’ effectiveness because of its comprehensiveness. Also, based on the DTF dimensions, more improvements and studies should be conducted to ensure students' success, in relation to understanding complicated content like Fiqh Muamalat. Future study should focus on comparing different teaching frameworks vs DTF.